FITNESS FOR SERVICE OF PIPING SYSTEM DUE TO GENERAL METAL LOSS AND LOCAL METAL LOSS BASED ON API RP 579 STANDARD - PISANTIADIPUTRA (NIM : 13105091); Pembimbing : Prof. Dr. Ir. IGN. Wiratmaja Puja, MIKKO
The operating pipe will be passed by fluid flowing through inside or outside the surface. This interaction with fluid could cause the corrosion defect. The defects will resulting the wall thinning and degradation on the pipe, thus reducing the strength and the maximum operating condition of the pipe. Further, this depletion or wall thinning of the pipe will result in the occurrence of damage, so the evalutation step should be implemented to the component as a preventive method. The evaluation called as fitness for service assessment. This assessment related as the follow-up step in the RBI (Risk Based Inspection) to avoid failure or damage component caused by the degradation. This final task analyzed the fitness for service on degradated pipe subject to general metal loss and local metal loss based on Section 4 and 5 API RP 579. To help the analysis, calculation programs developed and used to evaluate level 1 and level 2 FFS assessment criteria on the pipe. As the case study, FFS analysis will be conducted at riser WHP-A Belanak for general metal loss case, and pipe zone 5 Farida C - Farica B for local metal loss case. The analysis of WHP-A riser results that the pipe acceptable in level 1 and 2 assessment criteria. The pipe could continue the operation with maximum operating pressure at 5925 psi for level 1 and 6613 psi for level 2. Meanwhile, the zone 5 pipe Farida C Ã‚Â– Farida B shows that the pipe do not acceptable in level 1 and 2 assessment criteria, but acceptable in level 3 assessment criteria. The difference on level 3 occurs because the load used in level 1 and level 2 assessment is the load in design condition, while the load used in level 3 assessment is the load in actual operating condition.